The critical role of research in diversity training: how research contributes to an evidence-based approach to diversity training. Issue 4 (2nd June 2014) - Nguyen, Steve
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The purpose of the paper is to outline a diversity training framework in which research literatures and findings in psychology and human resource management (HRM) are used to guide organizations in the delivery of diversity training. The author proposes improvements to the current state of diversity training practices and implementations within organizations through the use and integration of research literature. Design/methodology/approach The paper is both a conceptual and a general review paper. It involves the discussion of research on diversity training, as well as diversity and training separately (conceptual), and includes a general analysis of diversity training (review). Findings The paper offers a general review about how psychological and HRM research findings can help organizations better implement diversity training. It suggests that successful diversity training involves a three-part approach: follow established psychological theory to guide selection of diversity training initiatives, use a framework for HR diversity management and adopt practical steps to better manage diversity initiatives (paying careful attention to a needs assessment, linking diversity strategy to business results and establishing metrics and evaluating effectiveness). Practical implications Diversity training has not been and continues to not be research- or evidence-based. This paper outlines some suggestions for integrating psychological and HRM research findings into the delivery of diversity training. The practical implication is that organizations and stakeholders will use a more evidence-based approach to diversity training. Originality/value This paper meets the needs of organizations seeking a more research- and evidence-based approach to diversity training.